Lean y construcción sostenible: una aproximación al bienestar laboral del trabajador de construcción - Carvajal-Arango, David; Vásquez-Hernandez, Alejandro; Botero, Luis Fernando Botero (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Sustainability considers a balance between the economic, social, and environmental dimensions, otherwise known as the triple bottom line. The economic and environmental dimensions have been widely studied, however, the social dimension, which is related to the workplace wellbeing of construction workers, has not been sufficiently addressed. Lean and Sustainable Construction philosophies have proven to be useful in reducing environmental, economic and social impacts of construction projects. For this reason, the objective of this study is to search within these philosophies, aspects and criteria aimed at increasing the wellbeing of construction worker.